2001
DOI: 10.1002/1097-4652(200104)187:1<11::aid-jcp1055>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic ribonuclease P: Increased complexity to cope with the nuclear pre-tRNA pathway

Abstract: Ribonuclease P is an ancient enzyme that cleaves pre-tRNAs to generate mature 5' ends. It contains an essential RNA subunit in Bacteria, Archaea, and Eukarya, but the degree to which the RNA subunit relies on proteins to supplement catalysis is highly variable. The eukaryotic nuclear holoenzyme has recently been found to contain almost twenty times the protein content of the bacterial enzymes, in addition to having split into at least two related enzymes with distinct substrate specificity. In this review, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 112 publications
0
35
0
1
Order By: Relevance
“…Extensive purification analysis of RNase P from HeLa cells has revealed that the nuclear form of this tRNA processing holoenzyme is composed of at least 10 protein subunits associated with a single RNA species, H1 RNA (Table 1; Eder et al+, 1997;)+ These protein subunits are designated Rpp14, Rpp20, Rpp21, Rpp25, Rpp29, Rpp30, Rpp38, Rpp40, hPop5, and hPop1 (Lygerou et al+, 1996b;Eder et al+, 1997;Jarrous et al+, 1998Jarrous et al+, , 1999avan Eenennaam et al+, 1999van Eenennaam et al+, , 2001)+ The tight association of these proteins with highly purified nuclear RNase P obtained by different purification schemes implies that they constitute the core structure of the holoenzyme )+ A recent study has shown that the mitochondrial form of HeLa RNase P possesses an RNA that is identical to the H1 RNA (Puranam & Attardi, 2001)+ This enzyme has a sedimentation coefficient of ;17S in glycerol gradients, compared to ;15S of the nuclear counterpart, and exhibits properties typical of a ribonucleoprotein enzyme (Puranam & Attardi, 2001)+ This finding contradicts earlier biochemical analyses that support the concept that human mitochondrial RNase P is not a ribonucleoprotein complex (Rossmanith et al+, 1995;Rossmanith & Karwan, 1998)+ These opposing findings provoke further debate on the biochemical nature of mitochondrial and other organellar RNase P enzymes (Frank & Pace, 1998;Schon, 1999;Altman et al+, 2000;Gegenheimer, 2000;Salavati et al+, 2001), and therefore more biochemical and genetic means should be applied to resolve this issue+ Nuclear RNase P purified from Saccharomyces cerevisiae has nine distinct protein subunits and genetic studies established that these subunits are essential for yeast viability and enzyme activity in tRNA processing (see Xiao et al+, 2001)+ A multi-subunit ribonucleoprotein has also been described for nuclear RNase P purified from Aspergillus nidulans (Han et al+, 1998)+ In addition to the protein subunits described above (Table 1), several other proteins transiently interact with RNase P in yeast and human cells+ As judged by twohybrid genetic screens in yeast, the subunit Rpp20 interacts with the heat shock protein Hsp27 and the subunit Rpp14 contacts several proteins, including the LIM domain protein 1 (LIMD1) and HSPC232 ; the latter is an SR-rich protein that exhibits partial similarity to splicing factors SC-35 and SRp46+ The interaction of Rpp20 with Hsp27 was verified by biochemical analysis )+ In S. cerevisiae, a complex of seven Sm-like proteins (Lsm2-8) is associated with the precursor RNA subunit, Rpr1, of nuclear RNase ...…”
Section: Ribonucleoprotein Complexes Of Rnase Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive purification analysis of RNase P from HeLa cells has revealed that the nuclear form of this tRNA processing holoenzyme is composed of at least 10 protein subunits associated with a single RNA species, H1 RNA (Table 1; Eder et al+, 1997;)+ These protein subunits are designated Rpp14, Rpp20, Rpp21, Rpp25, Rpp29, Rpp30, Rpp38, Rpp40, hPop5, and hPop1 (Lygerou et al+, 1996b;Eder et al+, 1997;Jarrous et al+, 1998Jarrous et al+, , 1999avan Eenennaam et al+, 1999van Eenennaam et al+, , 2001)+ The tight association of these proteins with highly purified nuclear RNase P obtained by different purification schemes implies that they constitute the core structure of the holoenzyme )+ A recent study has shown that the mitochondrial form of HeLa RNase P possesses an RNA that is identical to the H1 RNA (Puranam & Attardi, 2001)+ This enzyme has a sedimentation coefficient of ;17S in glycerol gradients, compared to ;15S of the nuclear counterpart, and exhibits properties typical of a ribonucleoprotein enzyme (Puranam & Attardi, 2001)+ This finding contradicts earlier biochemical analyses that support the concept that human mitochondrial RNase P is not a ribonucleoprotein complex (Rossmanith et al+, 1995;Rossmanith & Karwan, 1998)+ These opposing findings provoke further debate on the biochemical nature of mitochondrial and other organellar RNase P enzymes (Frank & Pace, 1998;Schon, 1999;Altman et al+, 2000;Gegenheimer, 2000;Salavati et al+, 2001), and therefore more biochemical and genetic means should be applied to resolve this issue+ Nuclear RNase P purified from Saccharomyces cerevisiae has nine distinct protein subunits and genetic studies established that these subunits are essential for yeast viability and enzyme activity in tRNA processing (see Xiao et al+, 2001)+ A multi-subunit ribonucleoprotein has also been described for nuclear RNase P purified from Aspergillus nidulans (Han et al+, 1998)+ In addition to the protein subunits described above (Table 1), several other proteins transiently interact with RNase P in yeast and human cells+ As judged by twohybrid genetic screens in yeast, the subunit Rpp20 interacts with the heat shock protein Hsp27 and the subunit Rpp14 contacts several proteins, including the LIM domain protein 1 (LIMD1) and HSPC232 ; the latter is an SR-rich protein that exhibits partial similarity to splicing factors SC-35 and SRp46+ The interaction of Rpp20 with Hsp27 was verified by biochemical analysis )+ In S. cerevisiae, a complex of seven Sm-like proteins (Lsm2-8) is associated with the precursor RNA subunit, Rpr1, of nuclear RNase ...…”
Section: Ribonucleoprotein Complexes Of Rnase Pmentioning
confidence: 99%
“…Six of the protein subunits of human RNase P have been shown to exhibit a moderate similarity at the primary amino acid sequence with their corresponding S. cerevisiae counterparts (Table 1), whereas the remaining subunits may exhibit some common biochemical and structural features+ Moreover, several Rpp subunits, including Rpp21, Rpp29, Rpp30, and hPop5, are conserved in archaea (Hall & Brown, 1999;Koonin et al+, 2001; Jim Brown, pers+ comm+)+ This unexpected conservation may indicate that these proteins have essential roles in RNase P function in tRNA processing (Table 1)+ Although some RNA subunits of archaeal RNase P are catalytic entities in vitro (Pannucci et al+, 1999), these conserved proteins may be essential for enzyme activity in vivo, as is the case with their homologs in yeast (see Xiao et al+, 2001)+ The conservation Notes: Pop7 is identical to Rpp2 (Stolc et al+, 1998) and Rpp29 is known as hPop4 (van Eenennaam et al+, 1999)+ Recombinant Rpp14, Rpp21, and Rpp29 bind to precursor tRNA, as judged by gel shift mobility analysis ; H+ Mann & N+ Jarrous, unpubl+ data)+ The genetic positions of RPP gene candidates on chromosomes have been identified by LocusLink search in the National Center for Biotechnology Information and by Blast searches of databases+ RPP21 resides in the MHC class I gene cluster near the HLA-E gene )+ Hsp27 stimulates RNase P activity )+ NS29 and NS38 are nucleolar localization domains+ Rpp29, Rpp38, and Pop1 may function in nucleolar localization of H1 RNA mediated by the P3 domain (Jacobson et al+, 1997;van Eenennaam et al+, 2000)+ Rpp38 has a conserved domain found in the ribosomal protein L7Ae/L30e/S12e/Gadd45 family and is predicated to bind an RNA secondary structure motif, K-turn, in the RNase MRP RNA (Klein et al+, 2001)+ As judged by immunoprecipitation experiments, RNase P and RNase MRP share several protein subunits, including Rpp20, Rpp29, Rpp30, Rpp38, hPop1, and hPop5 (van Eenennaam et al+, 2001)+ Rpp21, Rpp29, Rpp30, and Pop5 have homologs in archaea (Jim Brown, pers+ comm+; and CD-domain Search, NCBI)+ 2 N. Jarrous of protein subunits of nuclear RNase P in archaea is consistent with the idea that the nuclear RNA processing machinery in eukaryotic cells has an archaealrelated origin (Altman et al+, 2000;Horiike et al+, 2001)+ The eubacterial RNase P with its single protein component, C5, may then represent one specialized form derived from a more complex, ancient RNase P+ Alternatively, eubacterial RNase P may have additional subunits, other than the C5 protein, which are loosely associated with the holoenzyme (Stark et al+, 1978)+…”
Section: Conservation Of Protein Subunits Of Nuclear Rnase Pmentioning
confidence: 99%
“…13) Eubacterial RNase P is composed of a catalytic RNA and a single protein subunit, 14) while eukaryotic RNase Ps comprise a single RNA moiety and as many as 10 proteins; a highly purified nuclear RNase P from HeLa cells has at least 10 distinct protein subunits, termed Rpp14, Rpp20, Rpp21, Rpp25, Rpp29, Rpp30, Rpp38, Rpp40, hPop1, and hPop5. [15][16][17] Although Rpp21 and Rpp29 are known to be strongly involved in the catalytic activity of human RNase P, 18) the functional roles of other human RNase P proteins in RNase P have not been established. It was reported recently that Rpp20 and Rpp25, belonging to the Alba protein family, bind to each other, and that heterodimerization regulates their RNA-binding activity, subcellular localization, and expression, though their catalytic contribution to human RNase P remains unclear.…”
mentioning
confidence: 99%
“…Human nuclear RNase P appears to contain at least ten proteins (14-19). At least six of these proteins are homologs of integral RNase P subunits identified in Saccharomyces cerevisiae (2,(16)(17)(18)(19). The nuclear enzyme has been purified to homogeneity from S. cerevisiae (20), and shown to contain nine tightly associated proteins that are essential for RNase P activity and for life (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…ibonuclease P (RNase P) is an essential endoribonuclease that acts early in tRNA biogenesis to remove the 5Ј leader sequences of precursor tRNAs (pretRNAs) (1)(2)(3). The enzyme has been identified in every organism tested, in all kingdoms of life.…”
mentioning
confidence: 99%